2019
DOI: 10.3390/nu11030655
|View full text |Cite
|
Sign up to set email alerts
|

Mediterranean Diet and Cardiodiabesity: A Systematic Review through Evidence-Based Answers to Key Clinical Questions

Abstract: The Mediterranean Diet (MedDiet) has been promoted as a means of preventing and treating cardiodiabesity. The aim of this study was to answer a number of key clinical questions (CQs) about the role of the MedDiet in cardiodiabesity in order to provide a framework for the development of clinical practice guidelines. A systematic review was conducted to answer five CQs formulated using the Patient, Intervention, Comparison, and Outcome (PICO) criteria. Twenty articles published between September 2013 and July 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
72
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(76 citation statements)
references
References 78 publications
2
72
0
2
Order By: Relevance
“…In this sense, Southern Italy features examples of urbanization, where retail food is the most important source of food, which is the opposite to rural areas, where consuming locally grown, seasonal vegetables, as well as meat of courtyard animals is a fairly regular habit [28,29,37]. These contrasting local food environments, somehow superimposed on the Mediterranean diet, represent a unique setting to test the impact on health phenotypes, such as intermediate metabolism and cardiovascular risk [4,38,39].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this sense, Southern Italy features examples of urbanization, where retail food is the most important source of food, which is the opposite to rural areas, where consuming locally grown, seasonal vegetables, as well as meat of courtyard animals is a fairly regular habit [28,29,37]. These contrasting local food environments, somehow superimposed on the Mediterranean diet, represent a unique setting to test the impact on health phenotypes, such as intermediate metabolism and cardiovascular risk [4,38,39].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated that the Mediterranean diet significantly reduces the risk of developing metabolic syndrome (MetS) [1][2][3][4], a cluster of clinical conditions that occur together and increase the risk of heart disease, stroke, and type 2 diabetes [5][6][7]. However, the exact role of food retail and distribution in the risk of developing MetS has not yet been fully determined.…”
Section: Introductionmentioning
confidence: 99%
“…Also, adhering to this diet was associated with improvement in metabolic syndrome and type 2 DM in addition to healthy states mostly observed in both overweight and obese individuals. These findings signify the importance of implementing interventions in dietary factors even among DM patients in order to reduce the increasing rate of CVD mortality and morbidity [8]. Furthermore, several studies indicate the significance of these risk factors emerging especially in younger persons.…”
Section: Discussionmentioning
confidence: 81%
“…One of the most prevalent risk factors intensifying the severity of other major cardiovascular event risk factors like DM is related to dietary patterns and eating behaviors in a way that the term Bcardiodiabesity^has been introduced nowadays. Recently, a healthy diet named Mediterranean diet has been introduced and declared to be effective in terms of reducing CVD prevalence [8]. This diet mainly consists of foods containing high monounsaturated fat, low meat, and increased intake of whole grains, fruits, and vegetables [9].…”
Section: Discussionmentioning
confidence: 99%
“…16 By focusing pharmacists' education efforts on sleep, physical activity, and the incorporation of the cardiovascular riskereducing Mediterranean diet, pharmacists could have considerable impact on improving patients' cardiometabolic risk as well. 17,18 In addition, pharmacists can play a key role in increasing patient access to care and medication therapies. Community-based pharmacists can offer point-of-care testing services to identify patients with undiagnosed cardiometabolic conditions.…”
mentioning
confidence: 99%